Agricultural Market Integration in India - Andrle, Michal (IMF Working Papers; Working Paper, 2020)
We assess the degree of cross-market price discrepancy (a proxy for market integration), its evolution over time, and proximate determinants, using monthly price data for 21 agricultural goods and 60 markets in India. Econometric analysis shows that cross-market price integration is positively associated with the level of transportation infrastructure, and distance between market pairs. There is no robust evidence that price integration has increased in recent years, suggesting that any positive effects of recent policy initiatives are either small, outweighed by the identified determinants of integration, or yet to come.